Possible involvement of epithelial–mesenchymal transition in fibrosis associated with IgG4-related Mikulicz's disease. Issue 5 (September 2015) - Fukui, Masaki; Ogawa, Yoko; Shimmura, Shigeto; Hatou, Shin; Ichihashi, Yoshiyuki; Yaguchi, Saori; Hirayama, Masatoshi; Kawakita, Tetsuya; Tsubota, Kazuo
Abstract Objective. Immunoglobulin G4 (IgG4)-related Mikulicz's disease (MD) is a fibrosis-associated inflammatory disease, often accompanied by lacrimal gland swelling. Although much attention has been paid to the inflammatory aspects of this disease, the mechanisms of the fibrotic processes are still unclear. We focused on the fibrotic changes occurring in the lacrimal glands of IgG4-related MD patients, by examining molecules involved in the epithelial–mesenchymal transition (EMT). Methods. Lacrimal gland tissue specimens were obtained from 3 IgG4-related MD patients and 3 control patients with Sjögren's syndrome (SS). The glands were examined by immunohistochemistry and transmission electron microscopy. Results. Storiform fibrosis, a characteristic of IgG4-related MD, was observed in the lacrimal glands of IgG4-related MD, but rarely in those of SS. Reduced E-cadherin expression, increased phalloidin-stained filamentous actin, and increased α-smooth muscle actin, snail, and heat-shock protein 47 levels were observed in the lacrimal glands of IgG4-related MD compared with those of SS. Transmission electron microscopy revealed an abnormal periodicity of collagen bundles, and basal membrane thickening in the IgG4-related MD compared with that in the SS tissues. Conclusion. EMT-like changes were frequently observed in the lacrimal gland epithelia from patients with IgG4-related MD. Thus, EMT may be involved in the pathology of IgG4-related MD fibrosis.